2017
DOI: 10.1590/1806-9061-2016-0261
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Carcass Characteristics and Meat Quality of Griller-Type Broilers of Four Genetic Lines

Abstract: Griller-type chickens are broilers slaughtered between27and 29 days old weighing 1.3 to 1.5 kg and sold as a whole carcasses. The aim of the present study was to evaluate the growth performance, carcass traits, and meat quality of female broilers of four genetic lines reared for the production of griller-type chickens. A total of 960 broiler chicks was allotted in a randomized block design with four treatments and eight replicates of 30 birds per experimental plot. Each experimental treatment consisted of four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…Average daily feed intake, average body weight gain (BWG), average daily gain (ADG), feed conversion ratio (FCR; feed/gain), and viability were calculated as indicators of production performance following the formulas described by Marcu et al [34]. Production index (PI) was calculated following the formula of Barbosa et al [35]. Economic return indicators, such as feed cost per gain (FCG), salable bird return (SBR), net profit per bird (NPR), and return on investment (ROI) were calculated according to the formulas of Ojediran et al [36].…”
Section: Productive Performance and Economic Returnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Average daily feed intake, average body weight gain (BWG), average daily gain (ADG), feed conversion ratio (FCR; feed/gain), and viability were calculated as indicators of production performance following the formulas described by Marcu et al [34]. Production index (PI) was calculated following the formula of Barbosa et al [35]. Economic return indicators, such as feed cost per gain (FCG), salable bird return (SBR), net profit per bird (NPR), and return on investment (ROI) were calculated according to the formulas of Ojediran et al [36].…”
Section: Productive Performance and Economic Returnsmentioning
confidence: 99%
“…Hue angle and chroma were calculated according to Pathare et al [42]. Water holding capacity (WHC), such as drip loss, cooking loss, trawling loss, and roasting loss, was determined according to Barbosa et al [35].…”
Section: Hematology Carcass Meat Quality and Meat Fatty Acid Compositionmentioning
confidence: 99%
“…Ojediran et al (2016a) demonstrated that thigh weight was influenced by the lysine portion of the feed. According to Barbosa Filho et al (2017), there is a mathematical connection in carcass yield: low breast yield translates to a higher yield of other parts like shank, back and wings. This is similar to the report of Rance et al (2002).…”
Section: The Histological Observation Of the Livermentioning
confidence: 99%
“…Asimismo, se determinó la eficiencia de conversión alimenticia (ECA) con la fórmula utilizada por Sebola et al (2015), la cual se muestra a continuación: = Determinación de rasgos de la canal Esta fase del estudio fue realizada en el Laboratorio de Nutrición Animal del Colegio de Postgraduados, Campus Montecillo, Texcoco, México. Para evaluar las características de la canal se seleccionó aleatoriamente un individuo de cada grupo, considerando cinco hembras y cinco machos previamente sexados a través de evaluación visual y morfométrica (Arhin et al, 2018). Se midió el PC de cada ave y posteriormente fueron sacrificadas de manera convencional (aturdimiento, sangrado, desplume y evisceración).…”
Section: Evaluación Del Comportamiento Productivounclassified
“…Se midió el PC de cada ave y posteriormente fueron sacrificadas de manera convencional (aturdimiento, sangrado, desplume y evisceración). Se determinó el rendimiento de la canal (RCA) a través de la relación del peso de la canal caliente (eviscerado y sin considerar la cabeza, cuello y patas) y el PC del animal*100 (Barbosa-Filho et al, 2017). Para determinar la capacidad de retención de agua (CRA), pH y color se utilizaron las metodologías sugeridas por Guerrero et al (2002), las cuales se describen a continuación: Para evaluar la CRA se utilizaron dos muestras de 5 g/ave del músculo pectoralis major.…”
Section: Evaluación Del Comportamiento Productivounclassified